2021
DOI: 10.1007/s40670-021-01238-6
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Interdisciplinary Near-Peer Teaching Within Neuroanatomical Education—Preliminary Observations

Abstract: Near-Peer Teaching (NPT) is increasingly becoming an integral part of the medical curriculum. When considered alongside the increasing popularity of interdisciplinary education, it seems appropriate to explore NPT within an interdisciplinary context. In these observations, 3rd-year medical students taught 2nd-year psychology students neuroanatomy. The session was evaluated using three objective and subjective assays. A knowledge assessment test showed significant improvement after teaching, and there were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The Southampton NPT programme adopts a pedagogy rst approach and has subsequently published several studies indicating e ective knowledge gain following NPT sessions equal to that of faculty-led teaching sessions. (8,17,25) These studies have also demonstrated successful learning in an interdisciplinary context and show that students consistently prefer NPT led sessions to faculty teaching and perceive the sessions as more engaging, interesting and exciting. (8,17,25) Other examples of successful NPT programmes include using third and fourth-year medical students to teach musculoskeletal ultrasound, (14) and fourth-year students to facilitate diversity-focused case-based discussions.…”
Section: Current Examples Of Nptmentioning
confidence: 95%
See 2 more Smart Citations
“…The Southampton NPT programme adopts a pedagogy rst approach and has subsequently published several studies indicating e ective knowledge gain following NPT sessions equal to that of faculty-led teaching sessions. (8,17,25) These studies have also demonstrated successful learning in an interdisciplinary context and show that students consistently prefer NPT led sessions to faculty teaching and perceive the sessions as more engaging, interesting and exciting. (8,17,25) Other examples of successful NPT programmes include using third and fourth-year medical students to teach musculoskeletal ultrasound, (14) and fourth-year students to facilitate diversity-focused case-based discussions.…”
Section: Current Examples Of Nptmentioning
confidence: 95%
“…(8,17,25) These studies have also demonstrated successful learning in an interdisciplinary context and show that students consistently prefer NPT led sessions to faculty teaching and perceive the sessions as more engaging, interesting and exciting. (8,17,25) Other examples of successful NPT programmes include using third and fourth-year medical students to teach musculoskeletal ultrasound, (14) and fourth-year students to facilitate diversity-focused case-based discussions. (15) The latter example further illustrates an additional advantage of NPT, in that NPT may be used to facilitate socio-cultural diversity training.…”
Section: Current Examples Of Nptmentioning
confidence: 95%
See 1 more Smart Citation
“…Near-peer teaching (NPT) represents an alternative teaching approach that relieves the burden of traditional faculty-led teaching [ 13 ]. In this approach, the instructor is a person who is one or more years senior to another while being on the same level of educational training — for instance, senior medical students and junior medical students [ 4 , 5 , 14 16 ]. A large body of literature exists on NPT that spans across multiple domains, including general teaching, higher education, and, more recently, medical education [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature exists on NPT that spans across multiple domains, including general teaching, higher education, and, more recently, medical education [ 17 ]. Though a comprehensive review on NPT is beyond the scope of this paper, multiple randomized controlled trials, systematic reviews, quantitative studies, qualitative studies, and expert opinions have been published supporting the efficacy of NPT within medical education [ 16 , 18 23 ]. There are distinct theoretical features of NPT that underlie the effectiveness of this approach.…”
Section: Introductionmentioning
confidence: 99%